How to talk when kids won't listen ebook Whining, fighting, meltdowns, defiance, and other challenges of childhood. - Faber, Joanna (How to Talk., 2021)
An all-new guide from the mega-bestselling How To Talk series applies trusted and effective communication strategies to the toughest challenges of raising children. For forty years, readers have turned to Adele Faber and Elaine Mazlish's How To Talk So Kids Will Listen & Listen So Kids Will Talk , the book The Boston Globe called, "the parenting Bible," for a respectful and practical approach to communication with children. Expanding upon this work, Adele's daughter, Joanna Faber, along with Julie King, coauthored the bestselling book, How To Talk So Little Kids Will Listen . Now, Faber and King have tailored How To Talk 's tried and trusted communication strategies to some of the most challenging childhood moments. From tantrums to technology to talking to kids about tough topics, How To Talk When Kids Won't Listen offers concrete strategies for these and many more difficult situations. Part One introduces readers to the How To Talk "toolbox," with whimsical cartoons demonstrating the basic communication skills that will transform readers' relationships with children in their lives. In Part Two, Joanna and Julie answer specific questions and share relatable stories, offering practical tools for addressing issues such as homework hassles, sibling battles, digital dilemmas, problems with punishment, and more. Readers can turn directly to any topic of interest and find the help they need, with handy "reminder pages." Through the combination of lively stories from real parents and teachers, humorous illustrations, and entertaining exercises, How To Talk When Kids Won't Listen offers real solutions to struggles familiar to every parent, grandparent, teacher, and anyone else who lives or works with children.